(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
becoming one of the main priorities in planning the development of education. An integral and important part of these technologies is the computerization of the educational process. This process is accompanied by significant changes in the pedagogical theory and practice of the educational process associated with making adjustments to the content of learning technologies, which should be adequate to modern technical capabilities, and contribute to the harmonious entry of the child into the information society. Computer technologies were designed to become not an additional "makeweight" in teaching, but an integral part of the educational process, significantly increasing its effectiveness